Where women are leaders : the Sewa movement in India - Rose, Kalima; Self Employed Women's Association (Ahmadabad, India) (New Delhi : Vistaar Publications, 1992)
On the activities of Self Employed Women's Association, Ahmedabad, India.
Includes index.
Keywords: Self Employed Women's Association (Ahmadabad, India); Self-employed women -- India; Home labor -- India